2018
DOI: 10.1177/1932202x18775658
|View full text |Cite
|
Sign up to set email alerts
|

High School Teachers’ Perceptions of Giftedness, Gifted Education, and Talent Development

Abstract: figure, references, 62 titles.In the field of gifted education, there is little research on the perceptions of high school teachers of the gifted about giftedness, good gifted education practices, and the nature and needs of gifted learners. The purpose of this study was to form a deeper understanding of how those educators who guide gifted learners out of high school and into adulthood perceive giftedness and gifted education. This qualitative study, conducted in two phases, took place in a large suburban sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
6
0
2
Order By: Relevance
“…Tirri (2017) underscores that “teacher education is the key to changing the identification and teaching of the gifted” (p. 1). However, Russell (2018) found shocking results in his research, pointing to the fact that his qualitative study showed that high school teachers “did not read any research or literature on giftedness or gifted education” (p. 291). A notable finding of the study was in fact the overarching lack of knowledge in the field of gifted education.…”
Section: Teachers As Facilitators or Inhibitors Of Giftedness And Talent Developmentmentioning
confidence: 99%
“…Tirri (2017) underscores that “teacher education is the key to changing the identification and teaching of the gifted” (p. 1). However, Russell (2018) found shocking results in his research, pointing to the fact that his qualitative study showed that high school teachers “did not read any research or literature on giftedness or gifted education” (p. 291). A notable finding of the study was in fact the overarching lack of knowledge in the field of gifted education.…”
Section: Teachers As Facilitators or Inhibitors Of Giftedness And Talent Developmentmentioning
confidence: 99%
“…However, previous research also found some facilitators for implementing DI, such as colleagues, mentors, and control in decision-making (Bondie et al, 2019; Puzio et al, 2015). Hence, investigating barriers and facilitators while implementing DI for high-achieving students in mixed-ability classrooms might help support successful implementation in the future (Russell, 2018).…”
Section: Research On the Impact Of DI On Students’ Outcomesmentioning
confidence: 99%
“…Las creencias sobre AC han sido estudiadas en el ámbito escolar, a partir de las voces de docentes y directivos (Lassig, 2009;Long, 2012;Long et al, 2015;Rusell, 2018, García-Cepero & Iglesia, 2020. Respecto de los primeros, Al Zoubi (2018) encontró que algunas creencias se restringían a áreas académicas, mientras que otras incorporaban aspectos socioemocionales, como el desajuste social.…”
Section: Alta Capacidadunclassified